ECOBRICK-BASED SCHOOL WASTE MANAGEMENT EFFORTS (PLASTIC BRICK) IN IMPROVING LITERARY CULTURE - Suhendri, Edi (Jurnal EduHealth, 2022)
Plastic waste management is a never-ending problem, besides the increasing use of plastic-based materials in various places, is one of the main points that must be immediately eliminated so that the volume of plastic waste accumulation can be suppressed as small as possible. This study uses the school action method with a Research and Development approach, and the results of this previous study explain that the management of plastic waste in the SMP Negeri 23 Pekanbaru school environment through the ecobrick method has been successfully applied, the students and the teacher utilize the plastic waste into products. which have high value, for example, such as tables, benches, pots and several other school tools, the solution is considered very appropriate to be applied to students because in addition to reducing the accumulation of plastic waste in the school environment, it turns out that the ecobrick method can also be used as a learning medium. new to the students. The results of the application of other ecobrick methods can be seen from the construction of school facilities called literacy parks, and the literacy corner where the entire material framework comes from plastic waste that exists in the school environment and is successfully recycled in a simple way, to produce something that is useful, especially in terms of handling plastic waste and developing students' abilities through the ecobrick method